The Effectiveness of Grant Fund Management in Women’s Cooperatives and Islamic Savings and Financing Cooperatives (KSPPS) in Blitar City in Improving Cooperative Businesses and Members’ Welfare - Hardining Estu Murdinar; saifudin yusuf; wahidatun alfarda (Universitas Kadiri, 2026)
This study aims to analyze the effectiveness of grant fund management in Women’s Cooperatives and Islamic Savings and Financing Cooperatives (KSPPS) in Blitar City in improving cooperative business performance and members’ welfare. The research employs a quantitative approach with descriptive and explanatory research designs. The descriptive design is used to describe the implementation of grant fund management, cooperative business development, and the welfare conditions of cooperative members, while the explanatory design examines the influence of grant fund management effectiveness on business improvement and members’ welfare. The population of this study consists of administrators, managers, and members of Women’s Cooperatives and KSPPS receiving grant funds in Blitar City. Samples were selected using purposive sampling techniques. Data were collected through questionnaires, interviews, and documentation, and analyzed using descriptive statistical analysis and multiple linear regression. The results are expected to show that effective grant fund management, reflected in transparency, accountability, participation, and proper fund allocation, contributes positively and significantly to cooperative business growth and the improvement of members’ welfare. The findings of this research are expected to provide practical recommendations for cooperative management and policymakers in optimizing grant fund utilization to strengthen cooperative sustainability and improve community economic empowerment.